Gaming on the edge: Mobile labour and global talent in Atlantic Canada's video game industry. (30th April 2019) - Pottie‐Sherman, Yolande; Lynch, Nicholas
Abstract : Diminishing returns and advances in telecommunications have prompted large video game firms to seek new locations, outsource production, and develop niche studios, including on Canada's East Coast. In this paper, we examine emerging occupational cultures and trace the origins and evolution of video game production in Canada's Atlantic provinces—a critical yet peripheral space economy in the gaming sector. Our findings are drawn from 30 interviews with gameworkers, studio managers, government officials, and other industry experts. We find this industry to be driven by the confluence of three major factors: (i) provincial governments have supported video game development as a strategic industry via financial incentives; (ii) firms are benefiting from a return migration effect and are repatriating Atlantic Canadian talent from media hubs by selling "home, " work‐life balance, and an alternative to the punishing gamework culture associated with Silicon Valley; and (iii) post‐secondary institutions in the region have improved their talent pipelines through computer science, digital media, and video game development programs. Key Messages: Locations in Atlantic Canada are emerging as legitimate nodes in the global video game sector, supported by interactive digital media incentives and post‐secondary programs. The local gaming sector is engaged with a wider gaming habitus, including promoting place attributes and the return migration of Maritimers, Newfoundlanders and other gameworkers. The sustainability of the regional video game sector requires financial support that takes into consideration the local social, cultural, and economic contexts of gamework. Développer les jeux vidéo à la marge: le travail et les compétences mobiles dans l'industrie du jeu vidéo au Canada atlantique: La diminution du rendement et les progrès dans les télécommunications ont incité de grandes entreprises du jeu vidéo à chercher de nouveaux endroits où s'établir, à délocaliser la production et à développer des studios de niche, notamment sur la côte Est du Canada. À l'intérieur de ce texte, nous analysons les nouvelles cultures professionnelles dans le champ de la production des jeux vidéo et nous retraçons les origines et l'évolution de cette industrie dans les provinces du Canada atlantique. Il s'agit d'une activité économique essentielle pour la région, activité qui demeure tout de même périphérique considérant la localization des grandes entreprises dans le domaine. Nos conclusions sont tirées de 30 entrevues avec des travailleurs du secteur des jeux, des gestionnaires de studios, des fonctionnaires du gouvernement et d'autres experts de l'industrie. Nous concluons que cette industrie est mue par la confluence de trois facteurs majeurs : (i) l'appui financier des gouvernements provinciaux dans le développement des jeux vidéo à titer d'axe stratégique de développement; (ii) le phénomène de retour des travailleurs spécialisés provenant de la région qui sont à la recherche d'un meilleur équilibre travail‐famille et d'une solution de rechange à la culture ultra‐compétitive associée à la Silicon Valley; et (iii) l'augmentation du bassin de main‐d'œuvre relié à l'économie du savoir grâce à l'implantation de programmes en informatique, en média numériques et en développement de jeux vidéo dans les établissements d'enseignement supérieur des provinces atlantiques.